Simultaneously enhancing mechanical properties and electrical conductivity of aluminum by using graphene as the reinforcement - Zhang, Shuai; Chen, Gaoqiang; Qu, Timing; Fang, Gang; Bai, Shengwen; Yan, Yufan; Zhang, Gong; Zhou, Zhaoxia; Shen, Junjun; Yao, Dawei; Zhang, Yuanwang; Shi, Qingyu (Materials letters, 2020)
•Friction stir processing (FSP) was used to fabricate graphene/Al nanocomposite.•Uniform dispersion of graphene, clean and intimate interfaces were obtained.•Tensile properties and electrical conductivity of Al were simultaneously enhanced. In this study, we demonstrated simultaneously enhanced mechanical properties and electrical conductivity of pure aluminum (Al) by incorporating graphene as the reinforcement. The graphene/Al nanocomposite was fabricated by friction stir processing (FSP) combined with hot extrusion. It was found that graphene was homogeneously dispersed into Al matrix and directly bonded graphene/Al interfaces were formed, which were the structure basis for the simultaneously improved electrical and mechanical properties. This study provides new strategy for fabricating high-strength and highly conductive graphene/Al nanocomposites.